Marketing of Services by Developmental Financial Institutions - APSFC's Experience - Jagan Mohan Reddy, A.; James PremKumar, P. (Indian Journal of Marketing, 2004)
Economic Development of any country depends on the speed with which it could widen its industrial base, apart from laying sound infrastructure for the Agricultural Development. Though it is very often said that agriculture and industry are the two wheels of any economy and balanced development of both the sectors are essential, current experience shows that a strong, healthy, vibrant and diversified industrial base is a must for any country, if it wants to achieve economic development. If we agree that any country, which aims at the economic development, has to strive for rapid and diversified industrial development, the role of financial institutions in industrial development hardly needs any emphasis. Because in a country like India where planned efforts are on to develop a diversified industrial base, it is the Development Financial Institutions which initiate, nurse and sustain the industrial enterprises by providing the much needed financial support, presuming the availability of required human resources.